Clinical Profiles and Endoscopic Findings of Patients Undergoing Colonoscopy in Nobel Medical College (Journal of Nobel Medical College, 2019)
Background: Colonoscopy is an invasive procedure used both diagnostically and therapeutically. Direct visualization and real-time image of entire large colon and distal terminal ileum makes it superior. Patients are unable to undergo colonoscopy because of the limitation in the developing country. Moreover, limited studies are available in our country regarding the colonic diseases.Materials and Methods: It was a descriptive cross-sectional study done in Nobel Medical College Teaching Hospital, Biratnagar, Nepal from January 2018 to December 2018. Approval was acquired from Institutional Review Committee. All patients undergoing colonoscopy in the hospital was included. After taking proper consent, bowel preparation, premedications, colonoscopy was performed, findings noted in pro-forma.Results: Of the total 176 patients 119 (67.60%) were male and 57 (32.40%) were female; mean age 46.98 ± 17.13 years. Indication for performing colonoscopy was chronic diarrhea in 58(33.0%), chronic abdominal pain in 47(26.70%). Significant lesion observed in 142 patients (80.68%); colitis with unspecified etiology in 69 (39.20%), ulcerative colitis in 28 (15.90%), crohn’s disease in 13(7.38%).Colitis was more in male 46(66.67%) and involving rectum was common. Pan-ulcerative colitis was common seen in 11patients (39.28%).Conclusion: Chronic diarrhoea and chronic abdominal pain were two common indications. Male patients were in higher prevalence opting for colonoscopy. Colitis of unspecified etiology of rectum and ileo-cecal region was most common finding. Ulcerative colitis involving whole of colon and younger age group was predominantly affected.